NOVEL MUTATIONS OF THE G6PC GENE IN MALAYSIANS WITH GLYCOGEN STORAGE DISEASE 1a (GSD1a) - Abd Rahman, Amirah Assyiqqin; Abdullah, Ili Syazwana; Ser Huy, Teh; Khaidizar, Fiqri Dizar; Yap, Sufin; Wee Teik, Keng; Lock Hock, Ngu; Hui Bein, Chew; Pei Tee, Ong; Mohamed, Zulqarnain (Malaysian Journal of Science, 2021)
Abstract Glycogen Storage Disease 1a is a rare autosomal recessive disorder caused by mutations in the glucose-6-phosphatase gene (G6PC) encoding glucose-6-phosphatase (G6Pase), a key enzyme for the maintenance of glucose homeostasis. Deficiency of G6Pase underlies this disease associated with life-threatening hypoglycemia and growth retardation. To date, more than 110 mutations have be found worldwide.The aims of this study are to identify the mutations in G6PC gene in Malaysian GSD1a patients using standard molecular genetics methods and to determine the pathogenicity level of the novel mutations. We performed mutation screening for 21 GSD1a unrelated patients (Malay n=14; Chinese n=7) using Polymerase Chain Reaction (PCR) and DNA sequencing. Genomic DNA was extracted from patients’ peripheral blood and all five G6PC exons were amplified using specific primers. Nine mutations were found, in which five mutations have been previously reported and four are potentially novel mutations (H52L, K76X, P113S and A346P). To obtain further evidence on the potential pathogenicity of the novel mutations, restriction enzyme assay and TaqMan genotyping assay were designed to investigate its allele frequency in a panel of healthy individuals that serves as the control population samples (n=50 Malays, n=50 Chinese, n=50 Indians). Restriction enzymes MseI and MboI were used to assay the K76X and P113S mutations respectively. For the other two mutations (H52L and A346P), TaqMan genotyping assays was employed due to inavailability of a suitable restriction enzyme to distinguish between the normal and mutant sequences. Results obtained from both the restriction enzymes assays and the TaqMan assays showed that no mutant allele could be found in all 150 healthy individuals (300 alleles). In conclusion, four yet unreported mutations have been found in the Malaysian population, and these mutations are potentially novel pathogenic mutations. These finding provide support that the mutations spectrum of G6PC gene in Malaysia is heterogeneous, at least among the Chinese and Malay populations. KEY WORDS: Glycogen storage disease type 1a (GSD1a); glucose-6-phosphatase enzyme (G6Pase); Glucose-6-Phosphate catalytic subunit (G6PC).